Time, Space and People: Urban Archaeology and Urban Futures Paul Belford - Paul Belford (Internet Archaeology)
This article provides some personal reflections on a range of issues around urban archaeology, focusing on the contribution that the discipline can make to placemaking for future generations. These reflections are grouped into three thematic areas: time, space and people. It is argued that public engagement is critical for ensuring that archaeology realises its potential to influence future development positively.